2016
DOI: 10.3748/wjg.v22.i34.7841
|View full text |Cite
|
Sign up to set email alerts
|

Double-layered covered stent for the treatment of malignant oesophageal obstructions: Systematic review and meta-analysis

Abstract: AIMTo investigate the efficacy of double-layered covered stent in the treatment of malignant oesophageal obstructions.METHODSA systematic review and meta-analysis was performed following the PRISMA process. PubMed (Medline), EMBASE (Excerpta Medical Database), AMED (Allied and Complementary medicine Database), Scopus and online content, were searched for studies reporting on the NiTi-S polyurethane-covered double oesophageal stent for the treatment of malignant dysphagia. Weighted pooled outcomes were synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…The Niti-S design incorporates an inner dog-boneshaped NiTiNOL stent covered in a polyurethane layer surrounded by an uncoated NiTiNOL mesh (Fig. 11) [35,36]. The uncoated mesh allows tissue ingrowth to occur, thus improving anchorage and reducing the risk of stent migration.…”
Section: Anti-migratorymentioning
confidence: 99%
“…The Niti-S design incorporates an inner dog-boneshaped NiTiNOL stent covered in a polyurethane layer surrounded by an uncoated NiTiNOL mesh (Fig. 11) [35,36]. The uncoated mesh allows tissue ingrowth to occur, thus improving anchorage and reducing the risk of stent migration.…”
Section: Anti-migratorymentioning
confidence: 99%
“…The performed experiments have shown a suitable adherence of PUR coating to the stent surface, as well as improved biocompatibility and long-term stability comparing to the non-coated stents [18,[35][36][37][38]. Since the beginning of using polyurethane as a stent coating material (early 1990s), such stents were applied in coronary artery perforation [37], for treatment of esophagorespiratory fistulas [38,39], recurrent benign urethral stricture [40], malignant biliary [41,42], esophageal [43,44] or gastroduodenal obstruction [45], and irresectable esophageal carcinoma [46].…”
Section: Organic Coatingsmentioning
confidence: 99%
“…Systematic review and meta-analysis studies have demonstrated a technical success rate of virtually 100% and improvements in dysphagia scores by at least 2 points within 1–2 days of the procedure in > 95% patients (327282930). Self-expandable plastic stents (SEPS) are similar to SEMS with regard to relief of dysphagia in the short term, but adverse events such as migration occur more often with SEPS (31), making SEMS preferable over SEPS for palliating malignant esophageal strictures.…”
Section: Indicationsmentioning
confidence: 99%
“…In several randomized controlled trials, SEMS placement has been shown to provide superior efficacy to photodynamic therapy, laser therapy, and surgical bypass for the palliation of malignant esophageal strictures ( 21 22 23 24 25 26 ). Systematic review and meta-analysis studies have demonstrated a technical success rate of virtually 100% and improvements in dysphagia scores by at least 2 points within 1–2 days of the procedure in > 95% patients ( 3 27 28 29 30 ). Self-expandable plastic stents (SEPS) are similar to SEMS with regard to relief of dysphagia in the short term, but adverse events such as migration occur more often with SEPS ( 31 ), making SEMS preferable over SEPS for palliating malignant esophageal strictures.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation